Face and content validity for the special education leadership (Integration) questionnaire In Malaysia - Daud, Rohanida; Johari, Shazali; Abdul Hamid, Fazli; Syahrul Nizam, Junaini; Nordin, Mohd Norazmi (Karadeniz Technical University, 2021)
The validity of the face and content of a constructed set of questionnaires is very important in determining its validity and applicability. Each questionnaire that is constructed needs to go through this validity process to strengthen the strength of the questionnaire. The need in carrying out this validity is to meet the requirements ofthe objectives of the study as well as the integrity of an item constructed. This situation is very important in constructing a set of questionnaires related to special education leadership in scope in Malaysia. Therefore, this study was conducted to detail the face and content validity requirements conducted on the questionnaire related to special education leadership in Malaysia. The findings of this study can help subsequent researchers in determining the correct process in doing face and content validity.